Political Polarization During the COVID-19 Pandemic - Jungkunz, Sebastian (Frontiers in Political Science, 2021)
Affective polarization has increased substantially in the United States and countries of Europe over the last decades and the ramifications of the COVID-19 pandemic have the potential to drastically reinforce such polarization. I investigate the degree and dynamic of affective polarization during the COVID-19 pandemic through a two-wave panel survey with a vignette experiment in Germany fielded in April/May and July/August 2020. I 1) compare the findings to a previous study from 2017, and 2) assess how economic distress due to the crisis changes perceptions of other partisans. Results show that the public today experiences slightly stronger polarization between AfD voters and supporters of other parties. Yet, higher economic distress decreases the negative sentiment of voters of other parties towards AfD supporters. I argue that experiencing economic distress increases the awareness of political debate and the responsiveness to government decisions. Thus, in times of broad cross-party consensus, this can translate into public opinion so that it makes people less hostile towards other partisans.